2016
DOI: 10.1007/s11199-016-0623-0
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress and Sexual Satisfaction Among First-Time Parents: A Dyadic Approach

Abstract: The present paper reports on longitudinal associations between parenting stress and sexual satisfaction among 169 heterosexual couples in the first year after the birth of a first child. Actor Partner Interdependence Modeling (APIM) was used to model the effects of the mother’s and father’s parenting stress at 6 months after birth on sexual satisfaction at one year after birth. Based on social constructivist theory and scarcity theory, two hypotheses were posed: (a) mothers’ parenting stress will predict their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 60 publications
2
29
0
3
Order By: Relevance
“…Leavitt et al demonstrated that in a shift to parental Data are presented as mean ± SD. stage caused stress in the couple resulting in reduced sexual satisfaction (28). A meta-analytical study by Dillon and Beechler also reflected that the number of children had a negative effect on marital satisfaction (29).…”
Section: Discussionmentioning
confidence: 99%
“…Leavitt et al demonstrated that in a shift to parental Data are presented as mean ± SD. stage caused stress in the couple resulting in reduced sexual satisfaction (28). A meta-analytical study by Dillon and Beechler also reflected that the number of children had a negative effect on marital satisfaction (29).…”
Section: Discussionmentioning
confidence: 99%
“…Following other scholars in the field (e.g., Feinberg et al, 2010; Leavitt et al, 2016; Maas et al, 2015), we chose to use 27 items from the 36-item PSI Short Form due to lower factor loadings on 9 of the items, as was found by Abidin (1995). Items were averaged to produce an overall stress score (Cronbach’s alpha = .90 for mothers, .92 for fathers).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we also controlled for parenting stress which we measured using 27 items from the Parenting Stress Index (PSI; Abidin, ). Following other scholars in the field (e.g., Feinberg, Jones, Kan, & Goslin, ; Leavitt, McDaniel, Maas, & Feinberg, ; Maas, McDaniel, Feinberg, & Jones, ), we chose to use 27 items from the 36‐item PSI Short Form due to lower factor loadings on nine of the items, as was found by Abidin (). Items were averaged to produce an overall stress score (Cronbach's alpha = .90 for mothers, .92 for fathers).…”
Section: Methodsmentioning
confidence: 99%
“…HIV sero-positive women who had more children were less likely to be sexually assertive. This might be attributed to sexual health issues following child birth, motherhood responsibilities, and prioritizing the needs of children over sexual life, which is more pronounced in some cultures such as Iran (McDonald, Woolhouse, Brown, 2015;Azmoude et al, 2016;Arbil et al, 2017;Ghorat et al, 2017;Leavitt et al, 2017). Sexually non-assertive participants in our study had initiated sexual activities at younger ages compared to the assertive group.…”
Section: Discussionmentioning
confidence: 63%